Macroeconomics - Dornbusch, Rudiger; Bodman, Philip; Crosby, Mark; Fischer, Stanley; Startz, Richard (Australia McGraw-Hill, 2011)
Contains focus of the Chapter,Section Summaries,Key Terms,Graph It. The Language of Economics,Review of Technique,Crossword Puzzles,Fill-in-the-Blank Questions (10 per chapter),True/False Questions (10 per chapter),Multiple Choice Questions (10 per chapter),Conceptual Questions (3-6 per chapter),Technical Problems (2-5 per chapter),and answers to all questions and problems.
Include Glossary and Index.
Keywords: Macroeconomics -- Economic history -- Australia